DONALD TRUMP'S IMPACT: MEASURING STOCK REACTION AND CRYPTO ASSET VOLATILITY - I Kadek Bellyoni Dwijaya; Sri Dewi Fitrianingsih; Santi Rahmawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2026)
This study analyzes the impact of Donald Trump’s political dynamics on the Indonesian stock market and the volatility of global cryptocurrency assets. The objective is to compare the responses of both markets to major political events during the Trump 2.0 era. The study employs an event study approach, using the Wilcoxon test to examine stock abnormal returns and GARCH (1,1) and EGARCH models to analyze cryptocurrency volatility. The findings show that the 2024 U.S. presidential election and Donald Trump’s inauguration did not produce significant reactions in the average abnormal returns of Indonesian stocks. However, the announcement of import tariff increases in April 2025 generated a significant negative response in the short to medium term. In contrast, the cryptocurrency market experienced sharp increases in volatility around the election period, with strong evidence of volatility clustering. These results indicate that the Indonesian stock market is primarily driven by economic fundamentals, whereas the cryptocurrency market is more sensitive to political sentiment and pro-cryptocurrency figures. The findings support the semi-strong form of the Efficient Market Hypothesis and the Uncertain Information Hypothesis, highlighting the need for distinct investment strategies and improved financial literacy amid global political dynamics.